Eyecare practitioner perspectives and attitudes towards myopia and myopia management in the UK - Sophie Coverdale; Lindsay Rountree; Kathryn Webber; Matthew Cufflin; Edward Mallen; Alison Alderson; Neema Ghorbani-Mojarrad (BMJ Open Ophthalmology)
Objective Many children with progressive myopia are still prescribed single-vision correction. An investigation into UK eyecare practitioners’ (ECPs) perceptions of myopia management was carried out to ascertain factors which may be limiting its implementation and uptake within clinical practice.Methods and analysis Online focus groups were held with UK ECPs. Participants were encouraged to discuss their knowledge of the available myopia management options, their perception of how myopia management is being delivered in the UK and any barriers limiting ECPs' prescribing of these management options in practice. The discussions were transcribed and analysed thematically.Results Focus groups were held with 41 ECPs from primary and secondary eyecare. ECPs felt that provision of myopia management in the UK is variable. Most ECPs believe they have sufficient knowledge, but felt a lack of confidence in decision-making and practical experience. Less experienced ECPs sought more definitive guidance to support their decision-making. ECPs desired clarity on their duty of care obligations and were concerned over possible future litigation if they had not offered, or referred for, myopia management when indicated. The greatest barrier appears to be financial—treatment is expensive and ECPs are uncomfortable communicating this to parents. Many barriers were indicative of systemic problems within UK eyecare, such as commercial pressures, inadequate National Health Service funding and poor public awareness of paediatric eyecare.Conclusion Myopia management is not implemented consistently across the UK. To improve accessibility, changes are required at multiple levels, from individual ECPs through to wider stakeholders in UK eyecare provision.